Book review: laut bercerita, the sinking of untold tales - Wajdi, Majid; Putri, Erma Artajosi; Putri, Ni Putu Radha Savitri Maheswari; Ariyanti, Ni Luh Novia; Sinanditha, I Gede Bagus Ananda; Maharani, Anak Agung Radha Regita; Dewi, Ni Komang Mayang Saptariyasa; Riswana, I Gede Maryo Kanka (Journal of Language, Literature, Social and Cultural Studies, 2023)
Leila S. Chudori or full Leila Salikha Chudori (born December 12, 1962) is an Indonesian writer who has written works such as short stories, novels, and television drama scenarios. A few notes about Leila who was selected to represent Indonesia to receive a scholarship to study at "Lester B. Pearson College of the Pacific (United World Colleges)" in Victoria, Canada. Then, he continued to work as a journalist for the news magazine Tempo. She is also the winner of S.E.A. Write Award, is a tribute to writers and poets in Southeast Asia for her novel Laut Bercerita. It felt inspired by the kidnapping and enforced disappearance cases that occurred in 1998. In fact, before writing this novel, the writer conducted research interviews with one of the activists who had been kidnapped in 1998. Laut is the main character. Tells the story of a student activist during the New Order era, who was tortured and slaughtered to give testimony, then drowned along with a story that he had not had the chance to convey to Indonesia. Not only the advantages, this book also has disadvantages such as a slow storyline that tends to make the reader feel bored. Despite its flaws, this book has epic details, the characters in each character are built strongly, the events that really unfold, the deep meaning in each poem, and the selection of the right diction.